Effect of Garlic Powder Addition to Gelatin Biocomposite on Its Antibacterial Activity - Pramudita Putri Kusuma; Ganjar Fadillah; Husna Syaima; Teguh Endah Saraswati (ALCHEMY Jurnal Penelitian Kimia, 2016)
The addition of garlic powder to gelatin from chicken claw waste was potentially developed as a natural preservative in food, especially for meat. Preparation of gelatin/garlic biocomposite was performed in three stages: synthesis of gelatin from chicken claw, garlic powder preparation as allicin source and preparation of biocomposite gelatin/garlic. The preparation of dry biocomposites was done by weighing the gelatin and garlic powder in weight ratio of 1 : 1 and 1 : 2 (w/w) in the total mass of 0.75 grams. For wet biocomposite preparation, the mixture of the powder was solved in 5 mL of lactic acid 2 %. Functional groups of gelatin, garlic and biocomposite were analyzed by fourier transform infrared spectroscopy (FTIR). The antibacterial activity of biocomposite against Staphylococcus aureus were tested using disc diffusion method. This test was performed on garlic powder, solvent and gelatin/garlic biocomposites powder in the ratio of 1 : 1 and 1 : 2 in 2 % lactic acid solvent. The biocomposite with a weight ratio of gelatin : garlic of  1 : 1 had the optimum diameter of inhibition zone. The effectiveness of biocomposite gelatin/garlic as natural preservative applied in meat was also physically studied by organoleptic analysis. Organoleptic analysis through the hedonic test was conducted on the parameters of color, smell, and texture of gelatin/garlic biocomposites-coated meat. The results showed that the addition of garlic can increase the effectiveness of gelatin as a natural preservative of meat for four days stored in closed packaging at room temperature.